2002
DOI: 10.1177/009385402236735
|View full text |Cite
|
Sign up to set email alerts
|

A Prevention-Based Paradigm for Violence Risk Assessment

Abstract: The rationale for this article was to outline and describe an emerging model of prevention-based violence risk assessment and management and to discuss attendant clinical and research implications. This model draws on structured professional judgment rather than on actuarial prediction or unstructured clinical prediction. Its purpose is to prevent violence through the assessment of relevant violence risk factors and the application of risk management and intervention strategies that flow directly from these fa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
190
0
9

Year Published

2009
2009
2011
2011

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 220 publications
(207 citation statements)
references
References 71 publications
(107 reference statements)
8
190
0
9
Order By: Relevance
“…This finding corroborates the Structured Professional Judgment approach (Douglas & Kropp, 2002;Webster et al, 1997), which deliberately gives the assessor the opportunity to weigh the particular constellation of risk factors as well as any idiosyncratic risk factors for the client in his or her final professional risk judgment. Previous studies also showed such an incremental predictive validity for the final risk judgment (De Vogel & De Ruiter, 2006;Douglas, Ogloff, & Hart, 2003).…”
Section: Discussionsupporting
confidence: 74%
See 4 more Smart Citations
“…This finding corroborates the Structured Professional Judgment approach (Douglas & Kropp, 2002;Webster et al, 1997), which deliberately gives the assessor the opportunity to weigh the particular constellation of risk factors as well as any idiosyncratic risk factors for the client in his or her final professional risk judgment. Previous studies also showed such an incremental predictive validity for the final risk judgment (De Vogel & De Ruiter, 2006;Douglas, Ogloff, & Hart, 2003).…”
Section: Discussionsupporting
confidence: 74%
“…In addition, retrospective assessment of dynamic factors by researchers (as conducted by Gray et al, 2008, and many others), which is based on-probably limited-file information about the patient's functioning at that particular time, may be qualitatively different from the real time assessment by the treating clinician, advocated here. It may be different with respect to the information available to the assessor, the likelihood of bias due to the direct interaction between assessor and assessee (Philipse, Koeter, Van der Staak, & Van den Brink, 2006), and the opportunity to influence the predicted outcome by taking risk management measures (Douglas & Kropp, 2002).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations